Terapi Bermain Bagi Anak Tunarungu - Amalia, Rina Rizki (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2013)
Abstract: Child growth and development was normal treated like any other child. While the child growth and development running abnormally treated specially because they require the need of a special nature, they are the ones who then called the children with special needs (ABK). Belonging to one of the crew members is deaf child, the child who lost hearing ability either partially (hard of hearing) or completely (deaf). When we communicate or interact with deaf children, we treat it in a special way. There should also be special treatment for children with hearing that his hearing loss can be minimized, or even eliminated so that the child growing up to be normal. In this paper will discuss the handling of deaf children through play therapy which consists of two types of games. First, play activities can develop their hearing ability. Second, play activities can make children able to distinguish sounds and tones. Keywords: deaf, play, leader.